2021
DOI: 10.3390/ijerph18189523
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Violations of the International Code of Marketing of Breast-Milk Substitutes since the Adoption by the World Health Assembly in 1981: A Systematic Scoping Review Protocol

Abstract: This is the protocol for a scoping review that aims to systematically explore and summarise the published evidence of violations of the International Code of Marketing of Breast-milk Substitutes (the Code) and subsequent World Health Assembly Resolutions globally. The planned scoping review will seek to identify what research has been conducted on the topic, examine the geographic spread and nature of violations, and summarise knowledge gaps. The Code was adopted in 1981 by the World Health Assembly to protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Marketing of pacifiers was documented in countries where they are covered by the national law, such as Brazil (Bartolini et al, 2009; Lima, 2019; Lopes & Pereira, 2013; Rodrigues et al, 2021) and Vietnam (Durako et al, 2016). Marketing of CMF‐PW can be a channel for cross‐promotion to circumvent the Code (Nguyen et al, 2021; Zhao et al, 2019). Pacifiers and commercial milk formulas for mothers should be included in future guidance on the Code and countries should be encouraged to implement measures to restrict cross‐promotion through the marketing of these products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marketing of pacifiers was documented in countries where they are covered by the national law, such as Brazil (Bartolini et al, 2009; Lima, 2019; Lopes & Pereira, 2013; Rodrigues et al, 2021) and Vietnam (Durako et al, 2016). Marketing of CMF‐PW can be a channel for cross‐promotion to circumvent the Code (Nguyen et al, 2021; Zhao et al, 2019). Pacifiers and commercial milk formulas for mothers should be included in future guidance on the Code and countries should be encouraged to implement measures to restrict cross‐promotion through the marketing of these products.…”
Section: Discussionmentioning
confidence: 99%
“…11) and is reported in accordance with the Preferred Reporting Items for Systematic reviews and Meta‐Analysis (PRISMA) extension for Scoping Reviews (Tricco et al, 2018). The six‐step process of Arksey and O'Malley (Arksey & O'Malley, 2005) formed the framework and a protocol was published (Becker et al, 2021). The overall research question was identified as: What is the published evidence of exposure to violations of the International Code of Marketing of Breast‐milk Substitutes ?…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Code, BMS are all foods and beverages marketed for feeding infants and young children up to three years of age, including infant and follow-up formula, other milk products, bottle-feed complementary foods, feeding bottles, and teats. Since then, the WHA has adopted several subsequent relevant resolutions to clarify and strengthen aspects of the Code [ 10 ]. Up to March 2022, 144 (74.2%) of 194 WHO Member States have adopted legal measures to regulate BMS marketing aligned with the Code [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturers of commercial milk formula and foods for infants and young children recognise this gap in MIYCN education and fill it by providing training programmes and funding for pre-and in-service training, thereby creating a channel to market products and influence the attitudes, norms, and practices of health workers [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%